Pengaruh Motivasi Belajar dan Learning Engagement terhadap Hasil Belajar Peserta didik Kelas XI pada Materi Komputer Akuntansi di SMK Negeri 4 Surabaya - Amelya, Shella Amelya Renata; Rochmawati, Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2026)
Learning accounting on a computer using Accurate Online software requires not only technical skills, but also internal readiness on the part of learners in the form of motivation and active participation during the learning process. Practice shows that despite the use of technology and intensive practical exercises, learners' learning outcomes still vary. This study aims to empirically examine the contribution of learning motivation and engagement to learning success in computer-based accounting with Accurate Online. The study uses an associative quantitative design and involves 11th grade students majoring in accounting and finance at SMK Negeri 4 Surabaya. The sample was determined using a targeted sample selection applying the Slovin formula, with the number of respondents set at 84 students. The data was collected using a questionnaire to measure learning motivation and engagement, as well as a test to determine learning outcomes. The collected data was then transformed into a statistical processing and analysis procedure using multiple linear regression. The research results indicate a positive and statistically significant influence of learning motivation on the academic performance of students. Furthermore, learning engagement plays a positive and significant role in determining learning success. Simultaneous tests show that learning motivation, together with learning engagement, has significant predictive power for learning success. Thus, strengthening motivational aspects and systematically orchestrating learning engagement are strategic prerequisites for improving learners' academic performance.